Deposition of MgO Nanoparticles by Laser Pyrolysis - Abdulwaahb, Hala Mahmood; Rasheed, Bassam G.; Altawil, Hanadi H. (Al-Nahrain Journal for Engineering Sciences, 2022)
Magnesium oxide nanoparticles were deposited by laser pyrolysis process. Three types of lasers were employed CW CO2, Q-switched Nd-YAG (short pulses) and long pulses Nd-YAG lasers. The size and density of nanoparticles vary with laser energy, power, pulse duration and the scanning speed of the laser. In this method, MgO nanoparticles were deposited by a laser beam on a quartz substrate from aqueous solution of magnesium nitrate. AFM images reveal formation of small nanoparticle size of 24.5 nm with surface roughness 6.97nm by Q-switched Nd-YAG laser (10 ns) when the energy was 1J. While for CO2 laser, the smallest size was 18.8 nm at 0.4mm/s scanning speed with surface roughness 5.21nm at the same scanning speed. Moreover, long Nd-YAG pulses laser produces relatively larger average size of 37.5nm at 0.8ms pulse duration. The absorption spectra from UV-Visible spectroscopy were also conducted. The best absorption intensity was obtained at a wavelength ranging between 420-430 nm for both lasers. Finally, Thermal analysis using COMSOL Multiphysics software for the deposition process reveals that maximum temperature about 440Kfor Q-Switched Nd-YAG laser at 1J laser energy. While for RF CO2 laser, the maximum temperature obtained at 0.4mm/s scanning speed is 850K.This work provides a good knowledge for the deposition of nanoparticles using laser beams.